2009
DOI: 10.1063/1.3106762
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bond mediated transitional adlayer of glycine on Si(111)7×7 at room temperature

Abstract: The growth of glycine film by thermal evaporation on Si(111)7 x 7 at room temperature has been studied by X-ray photoemission. In contrast to common carboxylic acids, glycine is found to adsorb on Si(111)7 x 7 dissociatively through cleavage of a N-H bond instead of O-H bond. The intricate evolution of the observed N 1s features at 399.1, 401.4, and 402.2 eV with increasing film thickness demonstrates the existence of a transitional adlayer between the first adlayer and the zwitterionic multilayer. This transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(80 citation statements)
references
References 37 publications
10
70
0
Order By: Relevance
“…Moreover, there is a weak N 1s peak at ∼401.0 eV, which can be assigned to N···H−O feature. 10,11,33 For exposures in the transitional layer regime (i.e., above 45 s), the C 1s spectra have been fitted with four components at 284.5, 285.6, 286.6, and 289.2 eV, which are assigned to −CH 2 −S−Si, −CH 2 −SH, −CH 2 −NH−Si, and −COOH, respectively. 17,20 Further exposure to 2400 s increases the N 1s intensity of the N···H−O feature for transitional layer ∼14 times with respect to that for the 45 s exposure (Figure 2a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, there is a weak N 1s peak at ∼401.0 eV, which can be assigned to N···H−O feature. 10,11,33 For exposures in the transitional layer regime (i.e., above 45 s), the C 1s spectra have been fitted with four components at 284.5, 285.6, 286.6, and 289.2 eV, which are assigned to −CH 2 −S−Si, −CH 2 −SH, −CH 2 −NH−Si, and −COOH, respectively. 17,20 Further exposure to 2400 s increases the N 1s intensity of the N···H−O feature for transitional layer ∼14 times with respect to that for the 45 s exposure (Figure 2a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Scheme 1 shows the equilibrium geometries of the neutral and zwitterionic forms of the five benchmark proteinogenic biomolecules, which are obtained by DFT-D2 calculations. In our earlier study of glycine on Si(111)7×7, 34 we observed the existence of a transitional layer between the interfacial layer and zwitterionic layer for the first time. In our follow-up study of glycylglycine on the 7×7 surface, 35 we proposed a growth model involving sequential formation of the covalently bonded interfacial layer, the hydrogen-bond mediated transitional layer, and zwitterionic multilayers.…”
Section: ■ Introductionmentioning
confidence: 87%
“…The N 1s (Fig. 6 c) peak located at 400.4 eV could be assigned to neutral amino group -NH2 or N-H bond of amide bond present in the protein moiety [ 24,25,26 ].From the survey scan (Fig.6d) and spectrum of Ag 3d (Fig. 6 e) the binding energies of Ag 3d5/2 and Ag 3d3/2 are found to be at 368 and 374 eV, respectively[ 27,28,29,30 ].Therefore, it is concluded that the proteins were responsible for the bio-reduction of AgNO3 into AgNPs.…”
Section: Xps Of the Silver Nanoparticlesmentioning
confidence: 99%